Teaching Arabic Using the Language Immersion Method at University: Approaches and Implementation - Soleha, Siti; Agustin, Berlian Nestya; Huda, Mokhammad Miftakhul; Abdullahi, Zakariyya Muhammad; Dasuki, Moh.; Qomari, Nur (Program Studi Pendidikan Bahasa Arab, 2024)
Teaching Arabic in Indonesia often challenges fostering practical language skills, particularly at Islamic boarding schools (pesantren) and universities. The Language Immersion method, which involves intensively using the target language in natural situations, offers an appealing alternative to enhance Arabic proficiency. While several studies have discussed this method, there remains a gap in its systematic application in academic settings. This study aims to explore the approach and implementation of the Language Immersion method in Arabic teaching at UIN Kiai Haji Achmad Siddiq Jember. It employs a qualitative approach with a case study design. The research locus is the Arabic Language Education Program at UIN Kiai Haji Achmad Siddiq Jember, with lecturers and students as subjects. Data were collected through in-depth interviews, classroom observations, and documentation. Data analysis was conducted using data reduction, presentation, and conclusion-drawing techniques. The findings reveal that the language immersion method significantly improves Arabic students' speaking, reading, and listening skills. Through discussions, role-playing, and presentations, students learn contextually. However, challenges such as lecturer consistency, limited resources, and the need for Arabic-speaking environments outside the classroom must be addressed for optimal results.